Insight into the sulfur metabolism of Desulfurella amilsii by differential proteomics - Florentino, Anna P. (2019)
Many questions regarding proteins involved in microbial sulfur metabolism remain unsolved. For sulfur respiration at low pH, the terminal electron acceptor is still unclear. Desulfurella amilsii is a sulfur-reducing bacterium that respires elemental sulfur (S0) or thiosulfate, and grows by S0 disproportionation. Due to its versatility, comparative studies on D. amilsii may shed light on microbial sulfur metabolism. Requirement of physical contact between cells and S0 was analyzed. Sulfide production decreased by around 50% when S0 was trapped in dialysis membranes, suggesting that contact between cells and S0 is beneficial, but not strictly needed. Proteome analysis was performed under the aforementioned conditions. A Mo-oxidoreductase suggested from genome analysis to act as sulfur reductase was not detected in any growth condition. Thiosulfate and sulfite reductases showed increased abundance in thiosulfate-reducing cultures, while rhodanese-like sulfurtransferases were highly abundant in all conditions. DsrE and DsrL were abundantly detected during thiosulfate reduction, suggesting a modified mechanism of sulfite reduction. Proteogenomics suggest a different disproportionation pathway from what has been reported. This work points to an important role of rhodaneses in sulfur processes and these proteins should be considered in searches for sulfur metabolism in broader fields like meta-omics.